Metodologia de avaliação de implementação de programas e políticas públicas - Geisa do Socorro Cavalcanti Vaz Mendes; Mara Regina Lemes de Sordi (EccoS – Revista Científica)
The objective of this article is to place theoretical and conceptual reference mark for the study of programs, policies or educational projects implementation. Given the prominence of the assessment at the current public policies which associates certain ignorance of the involved social subjects verifies the need for studies that help to understand the evaluation process meanders passing through its model design to its implementation. The conceptions of assessment and policy/programs assessment are initially presented by discoursing over the evaluation functions, objectives and purposes. It is analyzed the difference between academic and evaluative research, focusing on the subjects that are involved in the process. Finally, it is highlighted the contributions of this methodology to the evaluation of program implementation or policies of institutional evaluation.